Pendidikan Gizi Seimbang dan Kesehatan Gigi Untuk Meningkatkan Pengetahuan Anak di SDN Wonosuko 2 - Wardhono, Adhitya; Qori’ah, Ciplis Gema; Nasir, M. Abd.; Prakoso, Bhim; Erzaldi, M Dwiki; Kumalasari, Nandya Alfina; Innabilla, Mirsya Rifah Aulia; Dewayani, Nyiur Rahma; Shafaana, Raihana Aulia; Ananta, Radina Widya; Puspitasari, Michele Stefany Nazwa; Puspito, Agung Nugroho (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Children of primary school age play an important role in future development, therefore the health of primary school children needs to be maintained and cared for properly. Nutrition and dental health problems in children are important issues that require serious attention, especially because of their impact on the physical growth and mental development of children later. Coordinating Minister for Human Development and Culture Muhadjir Effendy said that data from the prevalence of stunting touched 21.5% in 2023, and according to the 2023 Indonesian Health Survey (SKI), 82.8% of Indonesians have dental caries. Children aged 6-12 years have a high risk of developing dental caries, reaching 78.3% 84.8%. This shows the need for educational intervention in the community from an early age. The focus of this service program is to provide education related to balanced nutrition and dental health to increase the knowledge and awareness of students at SDN Wonosuko 2, Bondowoso Regency.